Caracterización de las empresas del departamento del Quindío que pueden incursionar en el mercado de valores, a través de la emisión de acciones en la bolsa de valores de Colombia (2012)
XBRL is emerging as a powerful international standard for efficient and effective scanning of any type of report issued by organizations (not just financial reports, as many would come to think). The XBRL standard organizational reports gives an "intelligent structure" that allows the stakeholder to use this information to avoid the problems commonly found in data manipulation, such as loss of valuable information, reprocessing of information, irrelevant information or unimportant to the stakeholder, and so on. The XBRL used for the approval of the information "taxonomies", which are the backbone of the standard as it is through this that can give meaning to information, as that allows different types of conversions to processing, transporting, or use the data in different ways according to the needs of those who possess it. The design of a taxonomy, besides being the most important activity for the standard implementation in organizations, regions or countries, is the key step in understanding how organizational information can be captured according to the standards for recognition, in means by which to use information technology and get the most out of not only the technology but the data contained in those reports. Now, make a taxonomy for the cash flow statement provides organizations a general idea of how this development can add value to the way in which financial statements are reflected as they are delivered to those in demand, especially with a been so important as mentioned. The document is an interesting starting point for future developments in this area.